Heat strain, volume depletion and kidney function in California agricultural workers - Moyce, Sally; Mitchell, Diane; Armitage, Tracey; Tancredi, Daniel; Joseph, Jill; Schenker, Marc (Occupational and environmental medicine (London, England), 2017)
BackgroundAgricultural work can expose workers to increased risk of heat strain and volume depletion due to repeated exposures to high ambient temperatures, arduous physical exertion and limited rehydration. These risk factors may result in acute kidney injury (AKI).MethodsWe estimated AKI cumulative incidence in a convenience sample of 283 agricultural workers based on elevations of serum creatinine between preshift and postshift blood samples. Heat strain was assessed based on changes in core body temperature and heart rate. Volume depletion was assessed using changes in body mass over the work shift. Logistic regression models were used to estimate the associations of AKI with traditional risk factors (age, diabetes, hypertension and history of kidney disease) as well as with occupational risk factors (years in farm work, method of payment and farm task).Results35 participants were characterised with incident AKI over the course of a work shift (12.3%). Workers who experienced heat strain had increased adjusted odds of AKI (1.34, 95% CI 1.04 to 1.74). Piece rate work was associated with 4.24 odds of AKI (95% CI 1.56 to 11.52). Females paid by the piece had 102.81 adjusted odds of AKI (95% CI 7.32 to 1443.20).DiscussionHeat strain and piece rate work are associated with incident AKI after a single shift of agricultural work, though gender differences exist. Modifications to payment structures may help prevent AKI.